Dinámicas de la conversación ideológica - Acosta González, Yoan Karell (Anales de la Academia de Ciencias de Cuba, 2022)
<p class="Texto-del-Resumen-y-Abstract" style="margin: 0px 0px 14px; padding: 0px; border-width: 0px; color: #000000; font-family: ’Roboto Light2001047’, sans-serif; font-size: 0.75em; font-style: normal; font-variant: normal; font-weight: 300; line-height: 1.444; orphans: 1; page-break-after: auto; page-break-before: auto; text-align: justify; text-decoration: none; text-indent: 0px; text-transform: none; widows: 1; letter-spacing: normal; white-space: normal; word-spacing: 0px; -webkit-text-stroke-width: 0px;">Objectives: to describe a set of discourse parameters revealing factors that either favor or hinder the success of a conversation in which ideology plays a major role, that is, an ideological conversation (IC); to offer a set of recommendations arisen from the results. Methods: the research is qualitative. Participant and non-participant observation as well as discourse analysis were used. The corpus was composed of multiple IC in which 27 individuals in total participated, throughout 2020 and the first half of 2021, in a context with certain political tensions in Cuba. Results: the analysis of a corpus of IC evidenced frequent factors that hinder the success of an IC. Some of them are: truth pretenses not supported by evidence, an evasive and justificatory posture toward dissonant truth pretenses, an inadequate posture toward misunderstandings, personal attacks against the interlocutor, pejorative valuation without argumentative solidity, gush expressiveness, among others. Conclusions: the most successful conversations within the corpus respected rules such as monitoring the control over emotions, listening attentively, avoiding personal attacks, being self-critical and critical in a respectful manner toward the interlocutor, being well-informed and providing evidence, pursuing a logical and critical thought, fighting cognitive bias, clarifying misunderstandings patiently, avoiding the assumption as an interlocutor of a discourse posture hinting at moral or intellectual superiority, verifying the knowledge one has or thinks one has, admitting and accepting undeniable truths even when they are dissonant regarding one’s own ideology, avoiding the discussion of too many topics at once, among others.